Analysis on the Influence of Different Setting Conditions on the Short Circuit Current Calculation Results of PSD-SCCP. Issue 1 (June 2020) - Wu, Jianbin; Zheng, Xiaoming; Gao, Yi; Zhao, Haibo; Wu, Zhong; Wang, Peng
Abstract: The result of power system short circuit calculation and verification is important reference for power system relay protection, electrical automatic device setting, transient process research, electrical planning and design and equipment selection. In the process of short circuit calculation, different conditional combination mode may lead to different results. The aggressive conditional combination mode will lead to the decline of power grid security performance, on the contrary, the conservative conditional combination mode will lead to the rapid increase of investment cost, resulting in a certain amount of investment waste. At present, there is no unified short circuit current calculation standard in the industry. Based on the actual power grid calculation example of a province in China, the short circuit current results of six condition combination modes is calculated and analyzed in this paper, expecting to provide an important reference for the setting of short circuit current calculation conditions.